Epilepsy Associated With Mitochondrial Encephalomyopathy, Lactic Acidosis, and Stroke-Like Episodes - Li, Jiaai; Zhang, Wuqiong; Cui, Zhitao; Li, Zhaoran; Jiang, Ting; Meng, Hongmei (Frontiers in Neurology, 2021)
Objectives: The present study explored the clinical characteristics and prognostic factors of epilepsy in patients with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes (MELAS). Methods: Thirty-four MELAS patients were included in the present study. They were diagnosed by clinical characteristics, genetic testing, muscle biopsy, and retrospective analysis of other clinical data. The patients were divided into three groups according to the effects of treatment after at least 2 years of follow-up. Results: Epilepsy was more common in male MELAS patients than in females（20/14）. The age of onset ranged from 0.5 to 57 years, with an average of 22.6 years. Patients with epilepsy and MELAS had various forms of seizures. Focal seizures were the most common type affecting 58.82% of patients, and some patients had multiple types of seizures. The abnormal EEG waves were mainly concentrated in the occipital (69.57%), frontal (65.22%) and temporal lobes (47.83%). Overall, the prognosis of patients with epilepsy and MELAS was poor. Poor prognosis was associated with brain atrophy (P = 0.026), status epilepticus (P < 0.001), and use of anti-seizure medications with high mitochondrial toxicity (P = 0.015). Interpretation: Avoiding the application of anti-seizure medications with high mitochondrial toxicity, controlling seizures more actively and effectively, and delaying the occurrence and progression of brain atrophy as much as possible are particularly important to improve the prognosis of patients with MELAS and epilepsy.